Teachers’ Contribution in Instilling Ideological Values of Islamic Education: A Case Study at SDN Lingkok Bunut - Didi Firmansyah; Ismail Thoib (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2026)
This study is motivated by the limited empirical research examining teachers’ roles as ideological agents in instilling Islamic ideological values within public elementary school settings. It aims to analyze teachers’ contributions, instructional strategies, and the contextual factors that influence the internalization of Islamic ideological values at SDN Lingkok Bunut, Indonesia. Adopting a qualitative case study design, the research involved 20 purposively selected participants, including the school principal, Islamic Religious Education teachers, classroom teachers, students, and parents. Data were collected through semi-structured interviews, non-participant observations, and document analysis, and were analyzed thematically to identify recurring patterns across data sources. The findings reveal that teachers contribute to value internalization through an integrated system comprising moral exemplification, habituation-based religious practices, value-oriented classroom interaction, experiential learning, and home–school collaboration. Islamic ideological values such as honesty, discipline, responsibility, humility, respect, and spiritual awareness are embedded across religious and general subjects as well as daily school routines. Strong leadership commitment and a supportive school culture emerge as key enabling factors, whereas diverse family backgrounds, digital influences, and limited instructional time act as inhibiting factors. These findings align with value internalization theory and teacher role theory, underscoring teachers’ credibility and professional agency as central to ideological education. The study concludes that Islamic ideological education can be effectively institutionalized in public elementary schools through strong leadership, a collaborative school culture, and teachers’ professional agency, and it contributes to the development of value internalization and teacher role theory while offering practical insights for strengthening character education in public schools.